Le novità normative nella lotta agli abusi sessuali a un anno dall’incontro in Vaticano del 2019 (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Introduzione - 2. I provvedimenti del 26 marzo 2019 - 3. Il Motu Proprio Vos estis lux mundi - 4. I rescritti del dicembre 2019 - 5. Conclusioni.The new regulations in the fight against sexual abuse one year after meeting in the Vatican in 2019ABSTRACT: In February 2019, Pope Francis chaired a meeting with bishops from all over the world at the Vatican to listen to the victims, reflect and seek increasingly suitable solutions in the fight against crimes of abuse of minors and vulnerable people. This text examines the norms issued by the Pope following that meeting for the Church, the Roman Curia and the Vatican City State and offers some food for thought for any future interventions.